Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

With the absorption law, I know I can do

$$P \land (P \lor Q) \equiv P$$

Can the same be applied like this?

$$(\lnot R \land P) \land (Q \lor P) \equiv P$$

Because, technically, I could move $Q$ to associate with the left parenthesis, and then switch its position with the first $P$, making this:

$$[(\lnot R \land Q)\land P] \lor P$$

Which looks a lot like the first scenario.

share|cite|improve this question
up vote 2 down vote accepted

No, that doesn't work. Each of $\land$ and $\lor$ are associative, but they don't associate together.

That's the same as ordinary arithmetic: $\times$ and $+$ are individually associative, but it's not true that $a\times(b+c)=(a\times b)+c$.

In your concrete example, note that $(\neg R\land P)\land(Q\lor P)$ is false when $R$ is true, no matter what $P$ is. So it can't be equivalent to $P$.

share|cite|improve this answer
Aaaand now I see why I failed the other exercises. Thank you. – Zol Tun Kul Sep 21 '13 at 2:21

A very good way to attack problems such as this to determine logical equivalence (or lack thereof) is to do it by assuming $P = T$ and $P = F$ and see if both sides are the same.

Suppose $P = T$ then let's evaluate $(\neg R\wedge P) \wedge (Q \vee P)$. This becomes

$$(\neg R \wedge T) \wedge (Q\vee T) = \neg R \wedge T = \neg R.$$

So as you can see it is dependent upon the truth of $R$. Thus it cannot possibly hold that $(\neg R\wedge P) \wedge (Q \vee P) \equiv P$. Just out of curiousity, let's work with the scenario that $P = F$ just to see what happens. Then

$$(\neg R\wedge P) \wedge (Q \vee P) = (\neg R \wedge F) \wedge (Q\vee F) = F \wedge Q = F = P$$

Even though it didn't work out in the case where $P = T$, it does work for $P = F$.

share|cite|improve this answer

To simplify $\;(\lnot R \land P) \land (Q \lor P)\;$, you can use the absorption law, but not in the way you asked about. Here are the detailed steps: \begin{align} & (\lnot R \land P) \land (Q \lor P) \\ \equiv & \;\;\;\;\;\text{"$\;\land\;$ is associative -- to prepare for absorption"} \\ & \lnot R \land (P \land (Q \lor P)) \\ \equiv & \;\;\;\;\;\text{"$\;\lor\;$ is symmetric"} \\ & \lnot R \land (P \land (P \lor Q)) \\ \equiv & \;\;\;\;\;\text{"absorption law -- exactly as you formulated it"} \\ & \lnot R \land P \\ \end{align} This cannot be further simplified to $\;P\;$, obviously.

Personally, when using logic instead of studying it, I leave the associativity and symmetry implicit, and just write something like \begin{align} & \lnot R \land P \land (Q \lor P) \\ \equiv & \;\;\;\;\;\text{"logic: use $\;P \equiv \text{true}\;$ on other side of $\;\land\;$; simplify"} \\ & \lnot R \land P \\ \end{align}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.